Intersectional Invisibility in Women’s Diversity Interventions - Wong, Chuk Yan E.; Kirby, Teri A.; Rink, Floor; Ryan, Michelle K. (Frontiers in Psychology, 2022)
Many diversity interventions for women are ineffective. One reason for this may be that the field that diversity interventions are usually based on, the social sciences, often do not consider intra-group differences among women. Specifically, differences by racialization may be excluded from such diversity interventions. The present research examines whether racially marginalized women have different diversity interventions needs than White women, and whether organizations are less likely to represent those needs (i.e., intersectional invisibility). Across an open-ended coding (n = 293) and a ranking study (n = 489), Black women noted a need to incorporate intersectional differences, Asian women prioritized methods to address challenges to their authority, and White women indicated a need to address agency perceptions. Improving work-life balance and networks was a shared concern among participants, though we theorized different racially gendered reasons for why these intervention needs are relevant to each group. In Study 3 (n = 92 organizations), we analyzed organizations’ websites using word count and textual analysis. Organizations— including the Education, Science, and Research sector— most readily advocated for women through enhancing agency. They were also less likely to mention dealing with perceptions of excessive agency or addressing intersectional considerations. The organizations broadly mentioned other marginalized groups besides women, but rarely did they do so intersectionality. Taken together, our findings demonstrate different intervention priorities across differently racialized groups. We found evidence of intersectional invisibility where organizations were more likely to address agency-enhancing intervention needs while failing to include other intervention needs relevant for Black women and Asian women. We discuss the implications of these findings for organizations, in general, as well as potential implications for the field of academic social sciences.